Tobacco extract-based biopesticide from cigarette butt waste for corn plants (Zea mays L.) - Nurhidayah Nurhidayah; Taufik Abdullah; Hijriati Sholehah; Fairuz Safhira (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
Cigarette butt waste can be used for biopesticides for environmentally friendly agricultural activities. Biopesticides cigarette can be produced by conducting a maceration extraction test using polar, non-polar, and semi-polar compounds and conducting a Mass Spectrometer Chromatography (GC-MS) test. This study aims to determine the effectiveness of bio-pesticide based on tobacco extract from cigarette butt waste for maize (Zea mays L.)